math

can you show me how to solve linear systems step by step?????
2x+y=5
x-y=1

  1. 👍 0
  2. 👎 0
  3. 👁 36
asked by heather
  1. Take the two equation two unknown down to one unknown by either adding or subtracting the second equation from the first so that one of the uknowns is removed.

    2x+y=5
    + x-y=1
    --------------
    3x=6
    x=2

    Then plug the newly found x value into one of the equations to find y. In this case:

    2(2)+y=5
    y=5-4
    y=1

    Verify by inserting the values for both x and y into the equations to make sure they work.

    1. 👍 0
    2. 👎 0
    posted by mtd

Respond to this Question

First Name

Your Response

Similar Questions

  1. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

    asked by Anonymous on October 25, 2018
  2. L Pre-Cal

    Hey! I'm getting stuck on how to solve this system of linear equations. Can anyone show me step by step Thanks! 3x-5y+5=1 5x-2y+3z=0 7x-y+3z=0

    asked by Norah on January 26, 2011
  3. math/algebra

    solve each of the following systems by substitution. 16) 5x -2y = -5 y - 5x = 3 20) 8x -4y = 16 y = 2x - 4 28) 4x -12y = 5 -x + 3y = -1 Step one: Solve on of the equations for one of the variables. y=2x-4 Step two:Substitute the

    asked by Diana on June 7, 2007
  4. Algebra help

    f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is from my book: step 1: 0=x^3-4x^2-x+4 step 2: 0=x^2(x-4)+(-1)(x-4) step 3: 0=(x^2-1)(x-4) I know how to solve once I get to step 3, but in step 2, I don't know what

    asked by Claure on June 16, 2009
  5. math

    An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

    asked by oscar on September 4, 2015
  6. math

    An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

    asked by oscar on September 4, 2015
  7. Physics

    Can someone please show me step by step how to normalize e^-5x in the interval (0, infinity)? I have read a lot of different books etc but need it explained to me in plain English or showed to me step by step because I am just not

    asked by Tammy on September 16, 2011
  8. Math

    I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 −

    asked by Ryan on March 30, 2017
  9. Math 7 A

    Note: For questions 5 and 6, remember to show all of the steps that you use to solve the problem. Be sure to use the text box where the question mark (?) first appears to show your mathematical work. You can use the comments field

    asked by jesse on November 20, 2017
  10. Algebra 1

    11n+23=3n-13+84 Solving multistep linear equations If someone could show me step by step how to do this it would mean alot god bless!

    asked by Angelina on August 22, 2016

More Similar Questions